Epitaxial array of Fe3O4 nanodots for high rate high capacity conversion type lithium ion batteries electrode with long cycling life. (August 2020) - Zhong, Gaokuo; Qu, Ke; Ren, Chuanlai; Su, Yong; Fu, Bi; Zi, Mengfei; Dai, Liyufen; Xiao, Qun; Xu, Jun; Zhong, Xiangli; An, Feng; Ye, Mao; et al.
Abstract: With the energy density of intercalation electrodes approaching the ceiling, there are tremendous interests in developing metal oxide conversion type electrodes for lithium ion batteries, which involve more lithium ions in electrochemical reactions. Nevertheless, the cyclic and rate performances of conversion electrodes are rather poor, due to their large volume changes during charging and discharging, poor contact with current collector, and accumulated internal passivation over cycling. Here by carefully designing epitaxial array of Fe3 O4 nanodots as a binder-free conversion electrode, we accomplish excellent rate performance under current density as high as 60C with long cycling life and good capacity, and the detailed scanning transmission electron microscopy in combination with comprehensive electrochemical analysis suggest that the success can be attributed to the synergic effects of released internal stress, slowed internal passivation, and good structure integrity all rendered by the nanodot array architecture of Fe3 O4 . Our study thus overcome materials breakdown, contact failure, and internal passivation of conventional conversion electrodes, providing new insight into optimizing conversion electrodes for practical applications. Graphical abstract: Image 1 Highlights: High quality epitaxial array of Fe3 O4 is fabricated by pulse laser deposition (PLD) on Cu current collector, enabling phase-pure and binder-free electrode with robust structure and interface integrity maintained during cycling. The Fe3 O4 array electrode delivers outstanding specific capacities of 501.5, 406.5, and 312.5 mA h/g under current densities of 10, 30 and 60C, and delivers a high specific capacity of 427.5 mA h/g up to 180 cycles at 10C, demonstrating its potential as high rate and high capacity electrode. The synergic effects of released internal stress, slowed internal passivation, and good structure integrity rendered by the nanodot array architecture of Fe3 O4, overcoming materials breakdown, contact failure, and internal passivation of conventional conversion electrodes that caused rapid capacity decay upon cycling.